Effect of ultrasound-guided peripheral nerve blocks of the abdominal wall on pain relief after laparoscopic cholecystectomy - Wu, Lining (J Pain Res, 2019)
Purpose: The aim of this study was to compare the effect of an ultrasound-guided transversus abdominis plane block (TAPB) and rectus sheath block (RSB) combination, an ultrasound-guided posterior TAP block combined with the local anesthetic infiltration (LAI) and LAI alone on pain relief after laparoscopic cholecystectomy (LC). Patients and methods: One hundred eighty patients who were American Society of Anesthesiologists class Ι or Π were included in this randomized, double-blind, non-inferiority study. All patients underwent three-port LC and were divided into 3 groups. The LAI group had ropivacaine mixed with dexmedetomidine injected around the trocar entrance site preoperatively. The TL group underwent ultrasound-guided posterior TAPB combined with LAI, and the TR group underwent ultrasound-guided TAPB combined with RSB. Postoperative pain was evaluated at the first, 4th, 8th, 24th, and 48th hours. If the visual analogue scale (VAS) score (including incisional pain, visceral pain or shoulder pain) was >3, intravenous dezocine (0.05 mg/kg) was injected slowly. Sleep quality, total consumption of dezocine and time to unassisted walking were recorded. The Global Satisfaction Score (GSS) for analgesia was also assessed within 48 hrs. Results: No difference was found in sleep quality, time to unassisted walking, or requirement for dezocine. We also found no difference in VAS scores at each time point within 48 hrs after LC among the 3 groups, but the GSS for analgesia in the LAI group was significantly increased within 48 hrs compared with the other two groups. Conclusion: Ultrasound-guided peripheral nerve blocks of the abdominal wall can significantly relieve postoperative pain in patients undergoing LC; however, patients receiving LAI expressed more satisfaction than patients in whom other methods were used. LAI is an easy and effective method that can be recommended for routine clinical practice in LC patients who are not converted to an open procedure.